Injectable Ternary Nanocomplex Hydrogel for Long-Term Chemical Drug/Gene Dual Delivery - Kim, Young-Min; Kim, Chang-Ho; Song, Soo-Chang (AMER CHEMICAL SOC, 2016)
We developed an injectable chemical drug/gene dual delivery platform system for long-term combination therapy. Ternary nanosized thermosensitive polymer/chemical drug/gene-(PCG) complexes showing sol gel transition were prepared by simple mixing of three components via hydrophobic and ionic interaction. The PCG complex hydrogel showed sustained release of chemical drug and genes for 40 days without denaturalization of genes in vitro. Dual delivery-mediated anticancer effects of PCG complexes were shown in vitro and in an in vivo xenograft model for up to 1 month. Therefore, this dual delivery platform is expected to be a new effective system for treatment of diseases via long-term chemical drug/gene combination therapy.
Keywords: CANCER; SYSTEM; CHEMOTHERAPY; THERAPY; SIRNA